Framing of Hamas Attacks on Israel in Al-Jazeera and BBCCoverage - Zawawi, Moh; Jambak, Mellinda Raswari; Hasanah, Ummi; Basid, Abdul; Anas, Khoirul (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. Digital media provides the latest news on global issues, particularly in the realm of religion, attracting a broad audience. This research explores how international mass media outlets Al-Jazeera and BBC frame their coverage of Hamas' attack on Israel on October 7. Utilizing a qualitative descriptive research method, the study aims to comprehensively depict the framing processes employed by Al-Jazeera and BBC in reporting on the Hamas-Israel conflict. Primary data includes Al-Jazeera's article "Why the Palestinian group Hamas launched an attack on Israel? All to know" and BBC News Indonesia's piece titled "What is Hamas and why is it fighting with Israel in Gaza?" Secondary data from relevant scholarly studies supports the research. Data collection involves reading and note-taking, while data analysis follows Miles and Huberman's model—data reduction, data display, and conclusion drawing. Findings reveal that Al-Jazeera defines Hamas' attack on Israel as a defensive measure, emphasizing its causes and making moral judgments by comparing Hamas' damage to Israel's actions. Al-Jazeera recommends characterizing Israel's actions against Palestine as genocide. On the other hand, BBC portrays Hamas' assault as sudden terrorism, neglecting Israel's criminal history. In its moral assessment, BBC focuses on Hamas' crimes to support a terrorist narrative. Treatment recommendations by BBC attempt to legitimize Israel's colonization efforts by highlighting that Palestine lacks recognition as an independent state by the UN. Differences in framing in the reporting of the Hamas-Israel conflict can affect diplomacy and peace efforts in the region as well as international support for one of the parties. International mass media are not always objective in reporting conflicts because they are influenced by political and ideological interests. This can lead to criticism of media objectivity and fairness and raises questions about the media's responsibility in shaping public opinion that can influence the development of conflicts.Keywords: Framing, Mass Media, Hamas Attack, Israel, Robert Entman